2012
DOI: 10.1007/s00232-012-9494-7
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Hepatoprotective Effects of Sesame (Sesamum indicum L.) in Carbon Tetrachloride-Induced Liver Toxicity

Abstract: More than 600 chemicals can cause damage in liver, one of which is carbon tetrachloride (CCl₄). Hepatoprotective agents could prevent tissue damage and reduce morbidity and mortality rates; such agents may include alternative or folkloric treatments. We investigated sesame (Sesamum indicum L.) for its hepatoprotective effect in CCl₄-induced experimental liver damage. To this end, 0.8 mg/kg of sesame fixed oil was provided intraperitoneally to rats whose livers were damaged by CCl₄. Tissue and blood samples wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…CCl 4 -induced liver injury is the most commonly used experimental model to evaluate the hepato-protective effect of natural products [28]. There are many side effects of Western medicines that have been reported for the treatment of liver injury [29]. Therefore, natural medicines have become a future potential therapeutic hope for controlling liver disease.…”
Section: Discussionmentioning
confidence: 99%
“…CCl 4 -induced liver injury is the most commonly used experimental model to evaluate the hepato-protective effect of natural products [28]. There are many side effects of Western medicines that have been reported for the treatment of liver injury [29]. Therefore, natural medicines have become a future potential therapeutic hope for controlling liver disease.…”
Section: Discussionmentioning
confidence: 99%
“…They are not quotable, produce incoherent toxicity, fail to generate a clinically significant lesion and require supportive therapy. Carbontetrachloride have e ARES between RES groups difference were significant (p<0.008); f K between RES groups difference were significant (p<0.008) the inconsistent results between experiments and across species (Cengiz et al, 2013, Wang et al, 2013. Lee et al (2012) reported that resveratrol treatment partially prevented carbon tetrachloride-induced acute liver damage (Lee et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there is no way to compensate for the absence of liver function in the long term and massive hepatic destruction often necessitates the need for liver transplantation [2]. There is therefore an intensive search of safe, affordable and readily available agents that can protect the liver from fulm inant damage [3]. Liver damage can be prevented by reducing the effect of reactive metabolites using antioxidants [4].…”
Section: Introductionmentioning
confidence: 99%